The Cerebral Cortex of the Pygmy Hippopotamus, Hexaprotodon liberiensis (Cetartiodactyla, Hippopotamidae): MRI, Cytoarchitecture, and Neuronal Morphology. Issue 4 (28th January 2014) - Butti, Camilla; Ewan fordyce, R.; Ann Raghanti, Mary; Gu, Xiaosi; Bonar, Christopher J.; Wicinski, Bridget A.; Wong, Edmund W.; Roman, Jessica; Brake, Alanna; Eaves, Emily; Spocter, Muhammad A.; Tang, Cheuk Y.; et al.
ABSTRACT The structure of the hippopotamus brain is virtually unknown because few studies have examined more than its external morphology. In view of their semiaquatic lifestyle and phylogenetic relatedness to cetaceans, the brain of hippopotamuses represents a unique opportunity for better understanding the selective pressures that have shaped the organization of the brain during the evolutionary process of adaptation to an aquatic environment. Here we examined the histology of the cerebral cortex of the pygmy hippopotamus (Hexaprotodon liberiensis) by means of Nissl, Golgi, and calretinin (CR) immunostaining, and provide a magnetic resonance imaging (MRI) structural and volumetric dataset of the anatomy of its brain. We calculated the corpus callosum area/brain mass ratio (CCA/BM), the gyrencephalic index (GI), the cerebellar quotient (CQ), and the cerebellar index (CI). Results indicate that the cortex of H. liberiensis shares one feature exclusively with cetaceans (the lack of layer IV across the entire cerebral cortex), other features exclusively with artiodactyls (e.g., the morphologiy of CR‐immunoreactive multipolar neurons in deep cortical layers, gyrencephalic index values, hippocampus and cerebellum volumetrics), and others with at least some species of cetartiodactyls (e.g., the presence of a thick layer I, the pattern of distribution of CR‐immunoreactive neurons, the presence of von Economo neurons, clustering of layer II in the occipital cortex). The present study thus provides a comprehensive dataset of the neuroanatomy of H. liberiensis that sets the ground for future comparative studies including the larger Hippopotamus amphibius. Anat Rec, 297:670–700, 2014. © 2014 Wiley Periodicals, Inc.